Unrelated cord blood compared with haploidentical grafts in patients with hematological malignancies. Issue 11 (3rd February 2015) - El‐Cheikh, Jean; Crocchiolo, Roberto; Furst, Sabine; Bramanti, Stefania; Sarina, Barbara; Granata, Angela; Vai, Andrea; Lemarie, Claude; Faucher, Catherine; Mohty, Bilal; Harbi, Samia; Bouabdallah, Reda; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Alternative donors, such as unrelated umbilical cord blood (UCB) and related haploidentical (haplo) donors, are more and more frequently searched for and used for patients who are candidates for allogeneic hematopoietic stem cell transplantation but are without a suitable related or unrelated donor. The aim of the current retrospective study was to compare the outcome of patients after haplo and UCB grafts prepared using a nonmyeloablative conditioning regimen. METHODS A total of 150 adult patients with high‐risk hematologic diseases who underwent allogeneic hematopoietic stem cell transplantation from alternative donors at 2 centers (Paoli‐Calmettes Institute [Marseille, France] and Humanitas Cancer Center [Milan, Italy]) were analyzed. Sixty‐nine patients had haplo donors and 81 patients had UCB donors. RESULTS The cumulative incidence of nonrecurrence mortality at 1 year was 23% in the UCB group versus 17% in the haplo group (P = .39). The incidence of grade 2 to 4 acute graft‐versus‐host disease and extensive chronic graft‐versus‐host disease in the UCB group versus the haplo group was 52% versus 29% (P = .05) and 12% versus 6% (P<.0001), respectively. The overall survival rate at 2 years was 45% in the UCB group (95% confidence interval [95% CI], 34%‐56%) versus 69% in the haplo group (95% CI, 58%‐80%) (P = .10). The progression‐free survival rate at 2 years was 36% in the UCB group (95% CI, 25%‐47%) versus 65% in the haplo group (95% CI, 53%‐77%) (P = .01). CONCLUSIONS The results of the current study suggest that for patients with high‐risk hematological diseases without a related or unrelated donor, haploidentical transplants are a promising alternative option that deserves further investigation. Cancer 2015;121:1809–1816. © 2015 American Cancer Society.